2006
DOI: 10.1200/jco.2006.06.8866
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Negative Lymph Node Count Is Independently Associated With Improved Long-Term Survival in Stage IIIB and IIIC Colon Cancer

Abstract: The number of negative nodes is an important independent prognostic factor for patients with stage IIIB and IIIC colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
246
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(268 citation statements)
references
References 32 publications
15
246
1
5
Order By: Relevance
“…This, along with the associated greater lymph node yield, may partially explain the high 5-year survival rates reported in Erlangen [13]. There was an increase in the number of negative lymph nodes with CME and CVL which has been linked to improved survival in both lymph node negative cases [14,15] and stage III disease [16]. West et al reported a greater lymph node yield (median, 30 vs. 18; p<0.0001) in high versus low ligation [13] In our study, the corresponding values are 33 and 25 (p= 0.048), thus establishing that high ligation produces oncologically superior specimen compared with standard low ligation surgery for carcinoma of the left colon and rectum.…”
Section: Discussionmentioning
confidence: 97%
“…This, along with the associated greater lymph node yield, may partially explain the high 5-year survival rates reported in Erlangen [13]. There was an increase in the number of negative lymph nodes with CME and CVL which has been linked to improved survival in both lymph node negative cases [14,15] and stage III disease [16]. West et al reported a greater lymph node yield (median, 30 vs. 18; p<0.0001) in high versus low ligation [13] In our study, the corresponding values are 33 and 25 (p= 0.048), thus establishing that high ligation produces oncologically superior specimen compared with standard low ligation surgery for carcinoma of the left colon and rectum.…”
Section: Discussionmentioning
confidence: 97%
“…There is a controversy, however, in the literature about whether the number of lymph nodes resected and evaluated impacts patient outcomes [29,30]. Further ambiguity exists even among the proponents of this quality metric regarding the exact number of lymph nodes needed to accurately stage a patient with colon cancer [5,[7][8][9][10][11][12][13][14][15][16][17][18]. Still, in the absence of a unique molecular signature of a colon tumor that dictates therapies and predicts a patient's course, the American College of Surgeons, ASCO, NCCN and others have adopted this as an indicator for quality assessment [24,26].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%
“…There has been great discussion and variability in the literature about the number of nodes that need to be examined to stage patients with accuracy [5,[7][8][9][10][11][12][13]. In addition, a substantial body of literature suggests that the absolute number of lymph nodes removed, whether positive or negative, is independently correlated with survival [14,15]. Furthermore, a number of studies have examined the ratio of positive lymph nodes to total number of lymph nodes as a predictor of survival [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…[6] According to the current Dutch guideline, the primary treatment for colon cancer is surgery, while adjuvant chemotherapy should be considered for patients with lymph node metastasis. Therefore, adequate lymph node evaluation is important in patients with colon cancer; [7][8][9] 10 or more lymph nodes should be evaluated for accepting N0 status. [10] However, regional population-based studies in the Netherlands showed large variation on the level of lymph nodes evaluated by pathologists and in the proportion of patients receiving adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%